Review of research into bioregenerative life support system(s) which can support humans living in space. (November 2021) - Liu, Hong; Yao, Zhikai; Fu, Yuming; Feng, Jiajie
Highlights: Analyzing research of bioregenerative life support system (BLSS) around the world, this article summarizes the theoretical/technological system framework and development path of BLSS, and proposes evaluation indices and the "three-stage" development path for extraterrestrial BLSS. To guide the establishment of Earth-based and extraterrestrial BLSS, this article proposes "three key conditions of BLSS gas balance", which is the key to the stability of BLSS. Abstract: To travel beyond the Earth and realize long-term survival in deep space, humans need to construct Bioregenerative Life Support System (BLSS), which reduces the requirement for supplies from the Earth by in situ regenerating oxygen, water and food needed by astronauts, and prevents pollution to extraterrestrial bodies by recycling waste. Since the 1960s, the USSR/Russia, the United States, Europe, Japan, and China carried out a number of studies with abundant achievements in BLSS systematic theories, plants/animals/microorganisms unit technologies, design/construction, and long-term operation/regulation. China's "Lunar Palace 365″ experiment realized Earth-based closed human survival for a year, with a material closure of >98%. However, a lot of research work is still needed to ultimately realize BLSS application in space, especially given the space experiment of BLSS never carried out, and the overall impact of space environment on BLSS unknown. Lunar exploration projects such as lunar village and lunar research station are successively proceeding. Therefore, future BLSS research will focus on lunar probe payload carrying experiments to study mechanisms of small uncrewed closed ecosystem in space and clarify the impact of space environmental conditions on the ecosystem, so as to correct the design and operation parameters of Earth-based BLSS. Such research will provide theoretical and technological support for BLSS application in crewed deep space exploration.